2011
DOI: 10.4028/www.scientific.net/amm.48-49.1389
|View full text |Cite
|
Sign up to set email alerts
|

Research on Health Monitor for Three-Dimensional Braided Composite Material

Abstract: This paper describes two methods of Fiber Bragg Grating (FBG) embedded in the three-dimensional (3D) braded composite materials and acoustic emission health monitor for 3D braided composite materials condition. The paper mainly analyses the relations of FBG change and the inner straining under the stretching on materials. It is provided that the way of signal collection and processing. The experimental results proved that FBG sensors have exceptional sense characteristic. The braided angle of composites has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…For example, Wu et al, 12 Gideon et al, 13 and Yang et al 14 demonstrated that the 3-D braided composite tube has excellent energy absorption capability and the interlacing point could effectively prevent yarns separating from the braided structure. Chen and Li 15 preformed a 3-D integrated braided tube with flange and Lu 16 designed a braiding method to prepare tube base plate. They all found that the connection region has high load carrying capacity due to the nonlaminated and integrated structure.…”
mentioning
confidence: 99%
“…For example, Wu et al, 12 Gideon et al, 13 and Yang et al 14 demonstrated that the 3-D braided composite tube has excellent energy absorption capability and the interlacing point could effectively prevent yarns separating from the braided structure. Chen and Li 15 preformed a 3-D integrated braided tube with flange and Lu 16 designed a braiding method to prepare tube base plate. They all found that the connection region has high load carrying capacity due to the nonlaminated and integrated structure.…”
mentioning
confidence: 99%